Antibacterial degradable magnesium alloy shovel needle and preparation method thereof
By using squid needles made of magnesium alloy materials containing Ag, Ca, Zn, and Cu, the risk of inflammatory reactions or infection caused by the long-term indwelling of traditional squid needle materials in the human body is solved, good biocompatibility and long-term antibacterial function are achieved, and the degradability and environmental protection of squid needles are ensured.
Patent Information
- Application Number
- CN202411645025.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
Long-term indwelling of traditional sulfone materials such as stainless steel in the human body may lead to inflammatory response or risk of infection, and lack good biocompatibility and long-term antibacterial functions.
The needle is made of magnesium alloy materials containing 1-5% Ag, 1-3% Ca, 0.1-1% Zn, and 0.1-2% Cu. The biocompatibility and antibacterial properties are improved through the alloying of these elements.
It provides good biocompatibility and long-acting antibacterial function. The needle can be degraded and absorbed in biological fluids. The service period is usually 3 days and the maximum period is no more than 1 week. The degradation process will not cause pollution to the environment.
Smart Images

Figure CN119506671A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable medical metal materials, and in particular to an antibacterial degradable magnesium alloy shovel needle and a preparation method thereof. Background Art
[0002] With the spread and popularization of Chinese medicine culture, shovel needle therapy, as an important part of Chinese medicine acupuncture therapy, has gradually entered the public eye. Shovel needle therapy, also known as intradermal needle therapy or buried needle therapy, is an extension of traditional acupuncture therapy. It mainly uses special needles to pierce the skin and fix it. By continuously stimulating the skin and meridians, it mobilizes the patient's meridians and qi and blood to achieve the purpose of treatment. However, traditional shovel needles have some shortcomings in medical applications. Traditional shovel needles are usually made of stainless steel or other metals. They may show good effects in the early stages of treatment, but long-term fixed retention in the human body may cause inflammatory reactions in surrounding tissues or cause infection and other risks. Therefore, it is particularly important to develop a shovel needle with good biocompatibility and long-term antibacterial function.
[0003] As a new type of biomedical material, magnesium alloy has received extensive attention in the field of medical devices in recent years. Magnesium alloy has excellent biocompatibility, which reduces the possible immune response and toxic reaction. The alkaline environment formed by the degradation of magnesium in the body has an inhibitory effect on the growth and reproduction of bacteria. Its degradation continuously releases magnesium ions and other active ions to promote cell proliferation and differentiation, thereby enhancing the therapeutic effect and achieving the purpose of eliminating pathogens. This characteristic gives magnesium alloy a unique advantage as a medical device material. As a needle used for intradermal treatment, the choice of material for the shovel needle is crucial to the treatment effect and patient comfort.
[0004] The subcutaneous degradability and biocompatibility of magnesium alloys have been confirmed, so their biosafety has been confirmed. However, existing magnesium alloy implants are mainly concentrated in two products: degradable bone screws and coronary stents. The service life of these magnesium alloy products is more than 3 months, and the time they stay in the body, such as bone screws, can exceed 1 year without being completely degraded. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an antibacterial and degradable magnesium alloy shovel needle and a preparation method thereof. The magnesium alloy shovel needle provided by the present invention has good biocompatibility and degradation performance, and its service life is usually 3 days and no longer than 1 week.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is an antibacterial and degradable magnesium alloy shovel needle, which comprises, by mass percentage, 1-5% Ag, 1-3% Ca, 0.1-1% Zn, 0.1-2% Cu, and the balance is Mg.
[0008] In some embodiments of the present invention, the degradable magnesium alloy shovel needle comprises, by mass percentage, 3-4% Ag, 1-2% Ca, 0.1-0.8% Zn, 0.1-1% Cu, and the balance is Mg.
[0009] In the present invention, the functions of each element are as follows:
[0010] (I) Improving the biocompatibility of magnesium alloys and imparting long-term antibacterial function
[0011] Calcium (Ca) is very abundant in the human body, and most of it is stored in bones and teeth, helping to maintain the structure and strength of bones and teeth. In addition, calcium is involved in many important physiological functions, such as nerve conduction, muscle contraction, blood coagulation, enzyme activation, etc. Therefore, calcium is essential for human health. Adding calcium to magnesium alloys can further enhance the biocompatibility of magnesium alloys.
[0012] Silver (Ag) is recognized to have the strongest broad-spectrum antibacterial ability and is one of the most promising antibacterial materials. Using Ag as an antibacterial factor will undoubtedly give Mg alloy excellent antibacterial ability, effectively avoiding the occurrence of cell or tissue infection around the implant.
[0013] (II) Improving the corrosion resistance of magnesium alloys and improving the mechanical properties of alloys
[0014] Zinc (Zn) can effectively improve the strength and hardness of magnesium alloys. By adding an appropriate amount of zinc, a solid solution and a precipitated phase can be formed, thereby improving the mechanical properties of the alloy. Secondly, zinc can also improve the corrosion resistance of magnesium alloys. Zinc can promote the formation of a dense oxide film on the surface of magnesium alloys, thereby improving the corrosion resistance of the alloy and extending its service life. This is of great significance for the application of magnesium alloys in the field of medical metal material technology. In addition, the addition of zinc can also improve the processing properties of magnesium alloys. An appropriate amount of zinc can refine the grain structure of the alloy, improve its plastic deformation ability, make magnesium alloys easier to die-cast, extrusion and other processing techniques, and make it easier to prepare into a shovel needle shape.
[0015] The addition of calcium (Ca) can effectively reduce the corrosion rate of the surface of magnesium alloys and extend their service life. The compound formed by calcium and magnesium can form a protective film on the surface of magnesium alloys, hindering further erosion by corrosive media. Secondly, magnesium alloys usually have low strength and plasticity, but adding an appropriate amount of calcium can improve the strength and plasticity of magnesium alloys. Calcium can form a solid solution with magnesium, increase the reasonable distortion of the lattice, and thus enhance the mechanical properties of magnesium alloys. In addition, under high temperature conditions, magnesium alloys are prone to solid solution precipitation, resulting in grain growth and reducing the strength of the material. The addition of calcium can inhibit the precipitation of solid solution, refine the grains, and form a stable dispersed phase, thereby improving the thermal stability of magnesium alloys.
[0016] Silver (Ag) has a high self-corrosion potential. Adding a certain amount of silver can improve the corrosion resistance of magnesium alloys and slow down the degradation rate in the human body fluid environment. By adjusting the proportion of Ag, the degradation rate of the obtained magnesium alloy shovel needle can be controlled to not exceed 1 week, meeting the use requirements of the shovel needle.
[0017] The second technical solution of the present invention is a method for preparing the above-mentioned antibacterial and degradable magnesium alloy shovel needle. After the above-mentioned components are prepared, the raw materials are melted, and then poured into a mold for cooling, extrusion, drawing, and shaping to obtain the antibacterial and degradable magnesium alloy shovel needle.
[0018] In some embodiments of the present invention, before melting the raw materials, a step of pretreating the raw materials is also included.
[0019] In some embodiments of the present invention, the pretreatment is cleaning and drying; the drying temperature is 90-110° C. and the drying time is 0.5-2 hours.
[0020] In some embodiments of the present invention, the atmosphere when the raw materials are melted is a mixed atmosphere of CO2 and SF6 in a volume ratio of 99.8:0.2.
[0021] The present invention discloses the following technical effects:
[0022] Conventional needles are usually made of stainless steel or other metals, which may show good effects in the early stage of treatment, but long-term fixed retention in the human body may cause inflammatory reactions in surrounding tissues or induce infection and other risks. The needle with good biocompatibility and long-term antibacterial function provided by the present invention selects three elements of silver, calcium and zinc as alloying elements, which has higher biosafety.
[0023] The degradable magnesium alloy shovel needle provided by the present invention can be degraded and absorbed in biological body fluids or blood environments, and its service life is usually 3 days and no longer than 1 week, which fully meets the use requirements of the shovel needle.
[0024] The degradable magnesium alloy shovel needle provided by the present invention will not cause pollution to the environment during the degradation process, which is in line with the concept of environmental protection. Compared with traditional non-degradable medical devices, the magnesium alloy shovel needle generates less waste during use, which helps to reduce the pressure of medical waste treatment.
[0025] The preparation method of the degradable magnesium alloy shovel needle provided by the invention is simple and does not require further surface treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is the antibacterial test of the magnesium alloy shovel needle of Example 1;
[0028] Figure 2 The degradation of the magnesium alloy shovel needle of Example 2 in the simulated body fluid;
[0029] Figure 3 These are SEM photographs of the magnesium alloy shovel needle of Example 3 after being immersed in Hank's solution for 10 hours (a), 20 hours (b), and 30 hours (c). DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The method for preparing the antibacterial and degradable magnesium alloy shovel needle of the present invention comprises the following steps:
[0036] (1) Weighing pure silver, pure calcium, pure zinc, pure copper and pure magnesium according to the ratio of 1-5% Ag, 1-3% Ca, 0.1-1% Zn, 0.1-2% Cu, and the balance Mg in the antibacterial and degradable magnesium alloy shovel needle;
[0037] (2) After washing the above materials, dry them in a drying oven at 90-110° C. for 0.5-2 hours;
[0038] (3) placing the dried pure magnesium in a low-carbon steel crucible and heating it in a resistance furnace at 710-730° C. for 20-30 minutes until the pure magnesium is completely melted;
[0039] (4) quickly adding dried pure silver, pure calcium, pure zinc and pure copper into the pure magnesium melt, melting and stirring evenly, and the protective gas atmosphere during the entire smelting process is a mixed atmosphere of CO2+0.2%SF (volume fraction, %);
[0040] (5) After all components are fully melted, the melt is poured into a pre-dried graphite mold to obtain a magnesium alloy material;
[0041] (6) extruding and drawing the magnesium alloy material to obtain a magnesium alloy wire;
[0042] (7) The magnesium alloy wire is bent and shaped into a shovel needle shape.
[0043] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0044] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0045] Example 1
[0046] The antibacterial and biodegradable magnesium alloy shovel needle provided in this embodiment is Mg1Ca0.2Cu0.5Zn3Ag (that is, in terms of mass percentage, it is 1% Ca, 0.2% Cu, 0.5% Zn, 3% Ag, and the balance is Mg).
[0047] The preparation method is as follows:
[0048] (1) Weigh pure silver, pure calcium, pure zinc, pure copper and pure magnesium according to the above proportions;
[0049] (2) After washing the above materials, dry them in a drying oven at 110° C. for 2 hours;
[0050] (3) placing the dried pure magnesium in a low-carbon steel crucible and heating it in a resistance furnace at 730° C. for 30 minutes until the pure magnesium is completely melted;
[0051] (4) quickly adding the dried other raw materials into the pure magnesium melt, melting and stirring them evenly, and the protective gas atmosphere during the entire smelting process is a mixed atmosphere of CO2+0.2%SF (volume fraction, %);
[0052] (5) After all components are fully melted, the melt is poured into a pre-dried graphite mold to obtain a magnesium alloy material;
[0053] (6) extruding and drawing the magnesium alloy material to obtain a magnesium alloy wire;
[0054] (7) The magnesium alloy wire is bent and shaped into a shovel needle shape.
[0055] This embodiment also provides a comparative example of pure magnesium and Mg0.5Zn (ie, 0.5% Zn by mass, with the remainder being Mg), and the preparation method is the same as that of Mg1Ca0.2Cu0.5Zn3Ag.
[0056] The antibacterial properties of the samples were evaluated by the plate coating method, and all samples and instruments were sterilized at high pressure and high temperature for 1 hour. The samples were placed in a culture dish, and 2 μL of Escherichia coli and Staphylococcus aureus bacterial suspensions were accurately measured and dropped on the surface of the samples with a pipette, and covered with plastic wrap to make full contact between the bacterial suspension and the sample surface. The culture dish was placed in a 37°C constant temperature incubator, and the samples were co-cultured with the bacterial suspension for 12 hours and then taken out. 20 mL of eluent was added to the conical flask, and the covered plastic wrap was placed in the eluent and stirred clockwise for 30 seconds, then allowed to stand and soak for 20 minutes. After the elution was completed, 2 μL of eluent was accurately measured with a pipette and dropped into the beef extract peptone medium, and the eluent was evenly spread on the entire medium plane using a sterilized glass rod. The culture medium of the sample was placed in a 37°C constant temperature incubator for 12 hours and taken out. The culture medium of the sample was placed in a 37°C constant temperature incubator for 6 hours, taken out, photographed and recorded, and then put back into the incubator. It was taken out at 12 hours to end the culture and observe the growth of the two bacteria. The experiment was repeated three times, and three samples were selected as parallel samples each time. The pure titanium matrix was the control group sample. The formula for calculating the sterilization rate of the experimental sample was: [(the number of colonies in the titanium matrix of the control group - the number of colonies in the experimental group) / the number of colonies in the titanium matrix of the control group] × 100%. The number of colonies was determined by the plate counting method. When the sterilization rate was higher than 90%, the sample was considered to have antibacterial properties. The results are shown in Figure 1As shown in the figure, according to the standard coating method, after 24 hours of experiment, the inhibition rates of pure magnesium, Mg1Ca0.2Cu0.5Zn3Ag and Mg0.5Zn against Staphylococcus aureus were 95.9%±0.1%, 98.7%±1.2% and 96.0%±0.7%, respectively. It can be seen that the addition of antibacterial elements Cu and Ag can improve the antibacterial properties of the material.
[0057] Example 2
[0058] This embodiment provides samples of 6 materials, namely: Mg, MgZn (i.e., 1% Zn by mass, with the remainder being Mg), Mg0.2Cu (i.e., 0.2% Cu by mass, with the remainder being Mg), MgCa0.5Zn (i.e., 0.5% Zn, 1% Ca by mass, with the remainder being Mg), Mg0.1Cu0.6Zn (i.e., 0.1% Cu, 0.6% Zn by mass, with the remainder being Mg), Mg2Ca0.3Cu0.8Zn2Ag (i.e., 2% Ca, 0.3% Cu, 0.8% Zn, 2% Ag, with the remainder being Mg by mass). The preparation method is the same as that of embodiment 1.
[0059] Effect verification
[0060] The degradation of different components in simulated body fluids is shown in Figure 2 The degradation of magnesium alloy is accompanied by the increase of pH. In the early stage of degradation, pH rises rapidly to above 11, and then slowly decreases. Before 70 hours, pH value slowly decreases to about 9.6. After 70 hours, with the increase of the type and content of alloying elements, pH suddenly drops sharply, and degradation accelerates. This indicates that at 70 hours, magnesium alloy material can maintain a relatively stable degradation process. After 70 hours, magnesium alloy degrades rapidly, and the increase of the type and content of alloying elements of the present invention is more conducive to the degradation of the material and human absorption after the shovel needle is in service. The degradation period of magnesium alloy in simulated body fluids is longer than the actual environment of human epidermis, so the magnesium alloy shovel needle of the present invention can guarantee a use time of 72 hours.
[0061] Example 3
[0062] The antibacterial and biodegradable magnesium alloy shovel needle provided in this embodiment is made of Mg3Ca0.1Cu0.6Zn3Ag (3% Ca, 0.1% Cu, 0.6% Zn, 3% Ag, and the balance is Mg in terms of mass percentage), and the preparation method is the same as that in Example 1.
[0063] SEM images of the sample after immersion in Hank's solution for 10 hours (a), 20 hours (b), and 30 hours (c) are shown in Figure 3In the first 10 hours, the shovel needle sample showed a relatively complete cylindrical appearance. As the immersion time increased to 20 hours, relatively evenly distributed corrosion pits appeared on the sample surface. After 30 hours, the corrosion pits gradually united together to form a larger gap, but the integrity of the cylindrical structure was still guaranteed. The magnesium alloy shovel needle showed overall degradation behavior, and there was no collapse of the overall structure. As the degradation progressed, its antibacterial properties would gradually be demonstrated.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antibacterial and degradable magnesium alloy shovel needle, characterized in that: The composition comprises, by mass percentage, 1-5% Ag, 1-3% Ca, 0.1-1% Zn, 0.1-2% Cu, and the balance is Mg.
2. A method for preparing the antibacterial and degradable magnesium alloy shovel needle according to claim 1, characterized in that: After the components in claim 1 are prepared, the raw materials are melted, poured into a mold, cooled, extruded, drawn, and shaped to obtain the antibacterial and degradable magnesium alloy shovel needle.
3. The method for preparing the antibacterial and degradable magnesium alloy shovel needle according to claim 2, characterized in that: Before melting the raw materials, the process also includes a step of pretreating the raw materials.
4. The method for preparing the antibacterial and degradable magnesium alloy shovel needle according to claim 3, characterized in that: The pretreatment includes cleaning and drying; the drying temperature is 90-110° C. and the drying time is 0.5-2 hours.
5. The method for preparing the antibacterial and degradable magnesium alloy shovel needle according to claim 2, characterized in that: The atmosphere when the raw materials are melted is a mixed atmosphere of CO2 and SF6 in a volume ratio of 99.8:0.2.